A Novel Multilayer Conically Squeezed Giant Electrorheological Fluid Damper. Issue 3 (March 2020) - Hu, Yingyi; Pu, Huayan; Sun, Yi; Ding, Jiheng; Wang, Min
Abstract: In this paper, a multilayer conically squeezed GER (giant electrorheological fluid) damper combined the characteristics of shear mode and flow mode is studied. Based on the theory of fluid mechanics, this paper established a simplified mathematical model of damper and had experiments to verify it. The result shows a good agreement and an effective isolation ability. With the simple structure, this damper has tunable ability of damping and stiffness to adapt to different application requirements.